Pengaruh Kualitas Pelayanan, Persepsi Harga dan Citra Merek terhadap Keputusan Tamu Menginap - Hafsah, Nur; Khalid, Jamaludin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of service quality, price, and brand image on guest stay decisions at The Sultan Hotel Jakarta. The background to this research is the increasing competition in the hotel industry, which demands that business owners understand the factors that influence consumer preferences and decisions when choosing accommodation. In this context, hotels are required not only to provide adequate facilities but also to deliver a superior service experience and build a positive perception of value in the eyes of consumers. The research method used was a quantitative approach with an accidental sampling technique. The sample consisted of 80 respondents who were guests who had stayed at the hotel. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 25. The analysis included validity, reliability, classical assumptions, t-tests, F-tests, and coefficients of determination to ensure the accuracy of the research model. The results showed that service quality, price, and brand image significantly influenced stay decisions, both partially and simultaneously (p<0.05). Service quality was the most dominant variable (β=0.103), followed by price perception (β=0.017) and brand image (β=0.012). These findings underscore the importance of improving service, setting competitive prices, and strengthening brand image to increase guest retention decisions.